Answer:
4(x-7)^2-(x-7)+3 (Assuming t is f)
Step-by-step explanation:
Let s(x)=x-7 and t(x)=4x^2-x+3 .
(t o s)(x)=t(s(x))=t(x-7)
Before I continue this means replace the orginal x in t with x-7.
This will then give you
4(x-7)^2-(x-7)+3
Answer:
4/6 and 6/15
Step-by-step explanation:
simplify all fractions to lowest possible.
4/6 = 2/3
10/25 = 2/5
6/15 = 2/3
4/6 and 6/15 are equivalent
Answer:
x = -2.585
Step-by-step explanation:
You will have to plug this into your graphing calculator.
In y=, type 5(1/2)^x in the Y1 and type 30 in Y2.
When you hit 2nd trace and hit find intersections, you will get (-2.585, 30).
The answer is x = -2.585